Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 1398 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Fungi", "Country is Mexico", "HasGeospatialIssue is true", "HasCoordinate is true" ] } The dataset includes 1398 records from 26 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0005269-150615163101818/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences